EKSPLORASI KONSEP MATEMATIKA KERAJINAN ANYAMAN BIDO PADA KEBUDAYAAN SUKU DAYAK SENGKUNANG DI KABUPATEN LANDAK - Wahyu Saputra; Ahmad Yani T; Silvia Sayu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this study was to determine the mathematical concepts contained in the craft of bido woven in the Dayak Sengkunang tribe culture in Landak Regency. The research method used is descriptive exploratory with ethnographic approach. The subjects of this study were 3 bido woven craftsmen with Dayak Sengkunang ethnic background and lived in Munggu Lumut Hamlet, Kayuara Village, Jelimpo District, Landak Regency. The data in this study are the results of interviews, observations and documentation. The results obtained from this study are the mention of numbers in local languages, namely original numbers including nye' for one, due' for two, taru for three, mpat for four, rima’ for six, inem for six, ijo’ for seven, mik' for eight, prue for nine and mporo' for ten. The activity determines the location of motifs in woven bido crafts using coordinate and symmetry systems. The results of the research also found that the concept of geometry with dimension 2 on the bido woven craft can be seen in the shape of the motif, which is a rectangular shape on the insert motif, reres due’and reres taru; build a square in the reres nye motif and insert it; build triangles on pogo’ motifs and insert; and build the trapezoid on the inline motif. Bido surface forms in the form of square and rectangular shapes. The measurement of materials using limbs such as hands is dapa’ and fingers are singap. All results obtained can be integrated in mathematics learning in schools.Keywords: Eksploration, Mathematics Concept